The patellar tendon bar! Is it a necessary feature? - Abu Osman, Noor Azuan; Spence, W.D.; Solomonidis, S.E.; Paul, J.P.; Weir, A.M. (2010)
The purpose of this investigation was to vary the load on the patellar tendon bar and to study the subsequent effect this has on the pattern of the pressure distribution at the stump-socket interface. Ten male subjects from the Southern General Hospital in Glasgow, UK participated in this study. Measuring systems utilising strain gauge and electrohydraulic technologies were designed, developed and constructed to enable pressure measurements to be conducted. One transducer, the patellar tendon (PT) transducer, was attached to the patellar tendon bar of the socket such that the patellar tendon bar was capable of being translated by +/- 10 mm towards or away from the tendon. The results of this study showed that the position of the patellar tendon bar had no significant effect on the pressure distribution around the socket indicating that it is an unnecessary feature, which, we propose, may be eliminated during manufacture of a trans-tibial socket. (C) 2010 IPEM. Published by Elsevier Ltd. All rights reserved.